Fertilitas Semen Kerbau Rawa (Bubalus bubalis carabanensis) yang Diencerkan dengan Pengencer Nira Aren (FERTILITY OF SWAMP BUFFALO SEMEN (BUBALUS BUBALIS CARABANENSIS) DILUTED WITH SUGAR PALM JUICE EXTENDER) - Rizal, Muhammad; Riyadhi, Muhammad (Jurnal Veteriner; Vol 17 No 3 (2016), 2016)
Sugar palm juice (Arenga pinnata Merr.) can be used as semen extender because its various nutrientscontent which were needed for spermatozoa preservation. The objective of this research was to examineeffectivity of sugar palm juice as swamp buffalo semen extender in artificial insemination (AI) program.Semen of swamp buffalo were collected by using an artificial vagina. Fresh semen were evaluated anddivided in equal volume into four tubes and diluted with lactose extender containing 20% egg yolk (lactoseor control), 85% sugar palm juice + 15% egg yolk (PJEY15), 80% sugar palm juice + 20% egg yolk (PJEY20),and 75% sugar palm juice + 25% egg yolk (PJEY25), respectively. Diluted-semen were preserved inrefrigerator at 5oC, and quality of spermatozoa including percentages of motile spermatozoa, livespermatozoa, and intact plasma membrane (IPM) were evaluated every day for four days. A total of 13female swamp buffaloes were estrous synchronize with PGF2a, and six buffaloes were inseminated withlactose and seven buffaloes were inseminated with PJEY20. Results of this research showed that at dayfourpreservation, mean percentages of motile and live spermatozoa for lactose (36.67 and 51.83%) andPJEY20 (35.83 and 51.5%) were significantly (P<0.05) higher than PJEY15 (31.67 and 44%) and PJEY25 (30 and 45.33%), but no difference significant between treatment for IPM parameter. Pregnancy rate forlactose was 66.67% and 71.43% for PJEY20. Percentage of birth for lactose and PJEY20 were 66.67% and71.43%, respectively. In conclusion, sugar palm juice could be used as an alternative extender in semenpreservation process and AI of swamp buffalo.
Keywords: palm juice, spermatozoa, artificial insemination, swamp buffalo